E-194 A randomized double-blind placebo-controlled trial of prophylactic antidepressant medication for the prevention of depression post aneurysmal subarachnoid hemorrhage. (23rd July 2022) - Keen, J; Lim, D; Prijoles, K; Haughn, H; Galang, C; Duboysky, A; Byun, E; Carroll, K; Kelly, C; Federico, E; Gonzalez, A; Levitt, M; et al.
Abstract : Introduction: Preventative antidepressant treatment is effective at reducing the rate and severity of depression after ischemic stroke, but little research has been done on the rate of depression in aneurysmal subarachnoid hemorrhage (aSAH) patients. To address the gap we conducted a prospective, double-blind, placebo-controlled, randomized trial of prophylactic antidepressant medication versus placebo after aSAH. Here we describe the protocol and report the population results. Methods: Patients 18 and older admitted for aSAH were included. The Montreal Cognitive Assessment was utilized to assess cognitive function, and patients scoring ≥20/30 were enrolled. Subjects were randomized to fluoxetine (20mg/day) or placebo for one year. Prior to discharge a baseline interview was conducted to assess levels of depression and anxiety, emotional and physical function, fatigue, sleep, and social support using a variety of validated instruments. Follow-up interviews with these assessments occurred at 6-weeks, 6-months, and 12-months. Results: We screened a total of 448 aSAH patients with 64 meeting enrollment criteria. Of those eligible, 5 were enrolled and 1 withdrew. Arms remain blinded; we therefore report the population results at baseline and at the 12-month follow up. Given the small sample, these results do not reach the standards of significance, thus we only describe the trends. Compared to baseline, patients at the 12-month assessments reported slightly higher depression scores (5.60 vs 6.58, PHQ-9), increased anxiety (5.60 vs 5.83, Hamilton Anxiety Scale), increased social support (6.40 vs 6.72, Multidimensional Scale of Perceived Social Support), decreased fatigue (2.80 vs 2.59, Fatigue Severity Scale), increased independence (83 vs 100, Barthel Index), increased emotional well-being (86.40 vs 88.67, SF36), increased role limitations due to emotional problems (86.67 vs 66.67, SF36), decrease in role limitation due to physical health (55.00 vs 66.67; SF36), increase in physical function (70.00 vs 98.75, SF36), moderate increase in energy/fatigue (51.00 vs 42.08, SF36), decrease in favorable general health (83.00 vs 77.08, SF36), and similar slight sleep disturbance (41.48 vs 42.60, PROMIS T-Score). Conclusions: The initial results of this ongoing study illustrate the feasibility and challenges of mental health screening and prophylactic randomized treatment in the acute care setting for post-SAH patients. Recruitment has been a challenge in this patient population. Here we describe the trends we see in outcomes at 12-months compared to baseline. These trends suggest that despite clinical improvement there may be an increase in depression and anxiety development one-year post-aSAH. Disclosures: J. Keen: None. D. Lim: None. K. Prijoles: None. H. Haughn: None. C. Galang: None. A. Duboysky: None. E. Byun: None. K. Carroll: None. C. Kelly: None. E. Federico: None. A. Gonzalez: None. M. Levitt: None. L. Kim: None.